Jezebel's Daughter - Collins, Wilkie, 1824-1889 (Salt Lake City, UT : Project Gutenberg, 2003)
"Jezebel's Daughter" by Wilkie Collins is a novel written during the late 19th century, specifically in the 1880s. The story revolves around the aftermath of two deaths, which intertwine the lives of their widows: Mrs. Wagner, who seeks to carry out her late husband$1 (Bs progressive business ideas, and Madame Fontaine, who is embroiled in a family scandal involving accusations against her character. The interactions between these strong female characters set the stage for themes of societal norms, maternal love, and the personal struggles of their respective families. At the start of the novel, the narrator, David Glenney, recounts significant events surrounding the deaths of Mr. Wagner and Doctor Fontaine that occurred on the same day. As David reflects on his association with Mr. Wagner's widow, we learn of her determination to implement her husband$1 (Bs progressive vision for advancing the roles of women in business. Concurrently, the narrative introduces Doctor Fontaine's widow and daughter, highlighting the complexities of their social standing and the prejudices they face. The emotional weight and character depth are further emphasized as Mrs. Wagner begins to understand and empathize with Madame Fontaine's situation, setting the groundwork for a gripping tale of intermingling lives and moral dilemmas in the face of societal expectations. (This is an automatically generated summary.)s
Release date is 2003-01-01
Produced by James Rusk. HTML version by Al Haines.
Keywords: British -- Germany -- Fiction; Widows -- Fiction; Germany -- Social life and customs -- 19th century -- Fiction; Death -- Fiction; Mental illness -- Fiction; Poisons -- Fiction